Community and government involvement in preserving the buatan barat boat in Southern Thailand - Abdul Wahab, Mohd Rohaizat; Ramli, Zuliskandar; Nik Abdul Rahman, Nik Hassan Shuhaimi; Abdul Samad, Mohammad Anis; Mohd Mokhtar, Ahmad Helmi (Springer Nature, 2018)
The traditional Malay boat is one of the Malay art objects that have now been gradually forgotten by the Malay community in the East Coast. Preservation of traditional boats is important to keep this cultural heritage from being vanished and constantly forgotten. The preservation of Buatan Barat boats made by the Malay community in Southern Thailand is one way to maintain the Malay cultural heritage. Even though there is no specific planning in preserving this heritage, the arising awareness in the community shows the existence of one main purpose, which is to preserve the Buatan Barat boat in Southern Thailand.